(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2018)
We worked on the basis of promoting the minimization of psychosocial risks in the teachers of Escuela Integral Bolivariana: "Rafael Rangel" II of the municipality Nirgua Yaracuy, through management strategies. The study was conducted under the modality of field research under the socio-critical paradigm, participatory action research method (IAP); taking the labor characteristics of 13 teachers during the 2012-2013 school year to be active in their duties. It concludes by highlighting the importance of disseminating information for the health of education workers and urging other researchers to address this issue to promote change. It is recommended that the director of the institution pursue the strategies implemented to consolidate a healthy life culture and act in a preventive manner in the face of threats to the health of the staff. The study was conducted under the modality of field research under the socio-critical paradigm, participatory action research method (IAP); taking the labor characteristics of 13 teachers during the 2012-2013 school year to be active in their duties. It concludes by highlighting the importance of disseminating information for the health of education workers and urging other researchers to address this issue to promote change. It is recommended that the director of the institution pursue the strategies implemented to consolidate a healthy life culture and act in a preventive manner in the face of threats to the health of the staff.